A new economic nationalism? Lessons from the PotashCorp decision in Canada - Sandy Walker (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
Foreign investors must be alert to the possibility that political sensitivities may impact foreign investment review processes, hence jeopardizing a small number of deals involving perceived national champions. One example, which underlines that politics can occasionally hijack the review of foreign investments, is the Canadian Government's rejection of BHP Billiton's takeover of Potash Corporation.
Keywords: 330